2003
DOI: 10.1067/mva.2003.114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of infrainguinal bypass grafting in patients with serologically proven hypercoagulability

Abstract: Patients with serologically proven hypercoagulability have inferior long-term patency, limb salvage, and survival rates after infrainguinal bypass. The high prevalence rate (13%) of diverse hypercoagulable states in this patient population supports serologic screening, especially in referral practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Four of these patients had a bypass failure, and all four had a known hypercoagulable disorder. Curi et al 25 have also suggested that the grafts of patients with a hypercoagulable state have inferior longterm patency; in their series, patients with hypercoagulability were also younger. Thus, younger patients presenting with lifestyle-limiting claudication or tissue loss should be evaluated for hypercoagulability before proceeding with revascularization.…”
Section: Discussionmentioning
confidence: 95%
“…Four of these patients had a bypass failure, and all four had a known hypercoagulable disorder. Curi et al 25 have also suggested that the grafts of patients with a hypercoagulable state have inferior longterm patency; in their series, patients with hypercoagulability were also younger. Thus, younger patients presenting with lifestyle-limiting claudication or tissue loss should be evaluated for hypercoagulability before proceeding with revascularization.…”
Section: Discussionmentioning
confidence: 95%
“…17 The recent publication by Curi et al reports that patients with hypercoagulability were more likely to have undergone prior revascularisation than patients deemed 'normal'. 29 The limitation of this retrospective analysis is that only 18% of the group underwent formal thrombophilia screening and so the normal group might contain patients with a thrombophilia defect and there might be an underestimation of the prevalence of 13%. Despite this limitation the 5-year primary patency of infrainguinal reconstructions was poorer in those with defined hypercoagulability (28% vs. 35% p ¼ 0:004).…”
Section: Thrombophilia and Failure Of Interventionmentioning
confidence: 98%
“…Thrombophilia defects are associated with failed revascularization in patients with peripheral vascular disease; the data suggest that the failure rate may be over three times higher than in patients without such defects1–9. Studies also suggest that hyperhomocysteinaemia is associated with vein graft stenosis10–12.…”
Section: Introductionmentioning
confidence: 99%